Morphology - Electrical Property Relations in Polymers - Phillips, P. J. (IEEE transactions on electrical insulation, 1978)
In a review of this length, it is impossible to include all relevant references to every section of a subject as large as that of electrical properties. I have, therefore, only presented the most pertinent references and have restricted the review to well-established facts. This has naturally excluded some of the very interesting, but controversial, subjects of present research. It should be clear from the review that researchers are only beginning to investigate morphological effects in some areas and that it will be some time before comprehensive investigations are reported. This is largely because polymer scientists familiar with morphology have rarely taken an interest in properties other than dielectric relaxation. The physicists and electrical engineers, who have generally carried out the research in other electrical properties, have had little knowledge of morphological detail. Paradoxically, those areas in which morphology is likely to be of greatest significance, electrets and breakdown, have received least attention. This review has endeavored to introduce the non-polymer scientist to morphology and to review, in a concise manner, well-established relations existing between morphology and electrical properties.